BASIC PRINCIPLES OF ECOLOGICAL TERRITORIAL ORGANIZATION OF URBAN PLANNING - Abdurahmonov Adkhamjon Sultonboyevich (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
In the article the main principles of the territorial organization of urban planning on an urban-ecological basis are studied and characterized.